Reflections about the holographic and non-holographic acquisition of surface topography: where are the limits? - Häusler, Gerd; Willomitzer, Florian (Light: Advanced Manufacturing, 2022)
Recording and (computational) processing of complex wave fields offer a vast realm of new methods for optical 3D metrology. We discuss fundamental similarities and differences between holographic surface topography measurement and non-holographic principles, such as triangulation, classical interferometry, rough surface interferometry and slope measuring methods. Key features are the physical origin of the ultimate uncertainty limit and how the topographic information is encoded and decoded. Besides the theoretical insight, the discussion will help optical metrologists to determine if their measurement results could be improved or have already hit the ultimate limit of what physics allows.
Created from Fastlane, Scopus look-up
Keywords: Holography; Optical metrology; Physical limits; Topography